Réponses

2013-05-13T20:29:26+02:00

Développemnt : 
5x ( 2x + 3 ) - ( 4x - 3 )( 2x + 3 ) = 0 
( 5x * 2x ) + ( 5x * 3 ) - [ ( 4x * 2x ) + ( 4x * 3 )] + [ ( -3 * 2x ) + ( -3 * 3 ) ] = 0 
( 10x² ) + ( 15x ) - [ ( 8x² ) + ( 12x ) ] + [ ( -6x ) + ( -9 ) ] = 0 
10x² + 15x - 8x² - 12x - 6x + 9 = 0 
2x² + 9x + 9 = 0 

Factorisation: 
( 2x + 3 ) * [ 5x - ( 4x - 3 )] = 0 
( 2x + 3 ) * [ 5x - 4x + 3 ] = 0 
( 2x + 3 ) * [ 1x + 3 ] = 0 
[ ( 2x * 1x ) + ( 2x * 3 ) ] + [ ( 3 * 1x ) + ( 3 * 3 ) ] = 0 
[ 2x² + 6 x ] + [ 3x + 9 ] = 0 
2x² + 6x + 3x + 9 = 0 
2x² + 9x + 9 = 0        (reponse pour ton exercice)